What Eve Did, What Women Shouldn’t Do: The Meaning of ΑΥΘΕΝΤΕΩ in 1 Timothy 2:12 - Perriman, A. C. (Tyndale bulletin, 1993)
1 Timothy 2:12, for obvious reasons, has suffered considerable scholarly buffeting in recent years. Careful lexicological investigations have undermined the traditional interpretation of αὐθεντέω as ‘to have authority over’ and brought to light various shades of meaning, without, however, clearly demonstrating their relevance to the passage. Thorough research into the religious environment of Ephesus has also suggested alternative perspectives, but again with doubtful exegetical validity. The argument of this paper is that if closer attention is paid to the structural and figurative character of the passage, a reading emerges which takes into account both the proper sense of αὐθεντέω and the particular circumstances under which Paul’s injunction was given.